APPLICATION OF STAD LEARNING MODEL ASSISTED MACROMEDIA FLASH IN HUMAN BLOOD CIRCULATION SYSTEM MATERIAL: PENGGUNAAN MODEL PEMBELAJARAN STAD BERBASIS MACROMEDIA FLASH PADA MATERI SISTEM PEREDARAN DARAH MANUSIA - Yolan Dunggio (LP2M Universitas Bina Mandiri Gorontalo, 2020)
Abstract This research is a Classroom Action Research (CAR) which is done in 2 cycles. The aim of this research is to know the application of cooperative learning model type STAD with macromedia flash in learning material about human blood circulation system to improve students’ learning result. Method in this research is qualitative method. The result of research shows that in teaching and learning activity, the activity of teacher in cycle I showed good and very good criteria with percentage 96.15% and the students’ activity showed good and very good criteria with percentage 73%. In the cycle II both of the teacher’s activity and the students’ activity got good and very good criteria with percentage 100%. The learning result in the cycle I, 57.89% of students got point under 70, in the cycle II got increase become 89.47% for the students’ who can pass the activity. Thereby, it can be concluded that by using cooperative learning model type STAD with macromedia flash can improve the students’ learning result in learning material about human blood circulation system. Keywords: STAD Learning Model, Macromedia Flash, Students’ Learning Result